Synthesis and formulation of self‐immolative PEG‐aryl azide block copolymers and click‐to‐release reactivity with trans‐cyclooctene. Issue 7 (3rd March 2021) - Dadhwal, Sumit; Lee, Arnold; Goswami, Shailesh K.; Hook, Sarah; Gamble, Allan B.
Abstract: Self‐immolative aryl azides can react with trans ‐cyclooctenes (TCO), triphenylphosphines or hydrogen sulfide (H2 S) to activate prodrugs, imaging probes and drug delivery systems. To date, the synthesis of polymers containing these aryl azide self‐immolative linkers and their reactivity with a strained alkene (i.e., in a bioorthogonal reaction) has not been explored. Also, due to the instability of aryl azides towards light and high temperatures, the polymerization methods compatible with aryl azides are limited. Through systematic investigation of the reversible addition‐fragmentation chain transfer (RAFT) and atom transfer radical polymerization (ATRP) methods, a self‐immolative PEG‐aryl azide block copolymer (PEG45 ‐ b ‐ABOC28 2 ) and a non‐responsive 4‐fluoroaryl block copolymer (PEG45 ‐ b ‐FBOC24 3 ) was prepared. ATRP provided the desired polymers in a highly controlled manner, whereas the RAFT conditions led to higher levels of aryl azide polymer degradation. The ATRP derived polymers 2 and 3 were formulated into nanoparticles of approximately 200 nm diameter, and particle triggering was demonstrated by the [3+2]‐cycloaddition reaction of TCO with PEG45 ‐ b ‐ABOC28 2 in solution (pure polymer) and as a formulated nanoparticle. Preliminary in vitro cell viability studies suggested that the stimuli‐responsive aryl azide polymers/nanoparticles are not cytotoxic up to 200 μg/ml concentrations. Abstract :